(untitled) (International Journal of Statistical Sciences, 2024)
Chao’s (1982) sampling scheme offers a systematic approach to select samples based on probability proportional to size (PPS) sampling without replacement but it might be difficult to grasp, particularly for entry-level researchers. In response, this study revisits Chao’s method with the aim of providing a simplified and more intuitive understanding. Drawing inspiration from efforts by Dr. Tommy Wright and subsequent group discussions with BKS, we present a step-by-step breakdown of Chao’s scheme with illustrative examples, emphasizing its elegance and practicality. This study showcases the value of making complex statistical methods accessible for broader engagement in research and practice. International Journal of Statistical Sciences, Vol.24(1), March, 2024, pp 133-154